Regulatory microRNA delivered to stallion spermatozoa during epididymal maturation - Twenter, Hannah, author; Bruemmer, Jason, advisor; Bass, Luke, committee member; Bouma, Gerrit, committee member; Coleman, Stephen, committee member (Colorado State University. Libraries, 2016)
Stallion spermatozoa are produced in the seminiferous tubules of the testis. After spermatogenesis, spermatozoa migrate through the seminiferous tubules to the rete testis then efferent ducts which converge to form a single duct within the caput of the epididymis. The epididymis is a convoluted tubule with region-specific luminal profiles. The epididymis consists of three commonly descried regions; caput, corpus, and cauda. Each region performs distinct functions in epididymal maturation of spermatozoa. The caput is responsible for concentration of spermatozoa by reabsorbing excess fluid from the epididymal lumen. The corpus is where majority of maturation occurs as spermatozoa gain motility and shed their cytoplasmic droplet. The cauda primarily serves as a storage site for the spermatozoa until ejaculation or spontaneous emission. All regions of the epididymis are lined with multiple epithelial cell types, each with different functions to provide the ideal luminal environment for the maturation. These epithelial cells also create apical blebs containing small, membranous vesicles named epididymosomes. The apical blebs are released from the apical surface via apocrine secretion and will disintegrate in the lumen, releasing epididymosomes. Epididymosomes transport proteins from the epithelium to the spermatozoa in the lumen. They also contain microRNAs (miRNAs). MicroRNAs are small, non-coding post-transcriptional regulators of mRNAs and can interfere with mRNA transcription through translational repression or degradation. We hypothesize that epididymosomes also transfer miRNA from the epididymal epithelium to spermatozoa. Quantitative real-time polymerase chain reaction was used to determine the miRNA profile of epididymal tissue from the caput and cauda, epididymal spermtozoa from the caput and cauda, and epididymosomes from the caput, proximal corpus, distal corpus, and cauda. Our focus turned to 33 newly-acquired miRNAs with expression specific to the spermatozoa located within the cauda as these are fully mature cells. Comparing the miRNAs present in each sample, 11 miRNAs had a distinct path from epididymal tissue to epididymosomes to spermatozoa, suggesting that miRNAs are transported to spermatozoa from the epididymal epithelium via epididymosomes. Pathway analysis was performed using DIANA tools on the 33 miRNA with expression on in caudal spermatozoa using an a posteriori method with predicted pathways considered significant with P≤0.05. Fifty-one predicted pathways were statistically significant. Some of those predicted pathways suggest a role in cell motility and viability, while others influenced factors in the oocyte or embryo. By developing a better understanding of the mechanisms behind the processes that regulate sperm maturation as well as the roles in embryogenesis better diagnostics for infertility in the horse may be generated.
Keywords: epididymosomes; microRNA; stallion; equine; epididymis; spermatozoa